Analisis Dampak Service Quality terhadap Customer Trust, Customer Satisfaction dan Customer Loyalty Bus Transjakarta - Noni Anche Natalia Fransisca; Yenita Yenita (LPPM Universitas BSI, 2023)
Transjakarta is one of the transportation modes used by people in the capital city. Since its inauguration since 2004 Transjakarta has experienced many changes in terms of service quality, therefore this research was conducted, with the aim of analyzing the effect of service quality on customer trust, customer satisfaction and customer loyalty of Transjakarta buses. To see the community's response to Transjakarta's ability to serve its customers is measured by Likert Scale with a score of 1 to 4. This research uses quantitative descriptive analysis method. Sample collection using purposive sampling with a total of eighty respondents. Data processing methods using SmartPLS. The results of this study indicate that there are two rejected hypotheses and four accepted hypotheses. The rejected hypothesis is: that the quality of service from Transjakarta will not have an impact on customer trust in using Transjakarta. Likewise, customer trust will not have an impact on customer loyalty in using Transjakarta. The accepted hypothesis is that the quality of services provided by Transjakarta has a positive impact both on customer satisfaction as well as on customer loyalty in using Transjakrta as daily transportation and then the satisfaction obtained from Transjakarta customers has a positive impact both on customer loyalty and also on customer trust in using Transjakarta.Â Â Â